THE IMPACT OF PROFITABILITY, LEVERAGE, AND LIQUIDITY ON BOND RATINGS OF FINANCIAL SECTOR FIRMS LISTED ON THE INDONESIA STOCK EXCHANGE - Thendrew, Owen; Osesoga, Maria Stefani (Universitas Multimedia Nusantara, 2024)
Abstract - This research was conducted to obtain empirical evidence regarding the effect of profitability, leverage, and liquidity on bond ratings. Bond ratings significantly influence funds raised from bond issuances, as a decrease can lead to undersubscription, while an increase can result in oversubscription. Investors should pay attention to bond ratings for informational materials and signals about a company's future obligations. This study's originality is rooted in its empirical examination of the key determinants—profitability, leverage, and liquidity—that affect bond ratings within Indonesian financial sector companies. Purposive sampling was used to choose the 19 financial sector companies, listed on the Indonesia Stock Exchange from 2019 to 2023, that released bonds and rated by PT PEFINDO in period 2020-2024. The analysis method used is ordinal logistic regression. The results of this study indicate that profitability and liquidity do not affect bond ratings, whereas leverage has a significant negative impact on bond ratings. Prioritizing equity-based funding sources, such as issuing shares, is advisable for the company. This approach will enhance the bond rating by reducing reliance on debt, thereby lowering the risk of default and minimizing capital-related financial risks. By strengthening its equity position, the company can improve its financial stability and foster long-term growth. Keywords: Bond Ratings; Leverage; Liquidity; Profitability